Eiger Adventure Communication Strategy at Women Jungle Survival Course (WJSC) Event - Eriani, Kerti; Sutarjo, Moch. Armien Syifaa (Jurnal Ilmiah Komunikasi Makna, 2025)
This research discusses the Eiger Adventure communication strategy in the Women Jungle Survival Course (WJSC) program. The aim is to understand and analyze the strategic steps taken by Eiger Adventure as a guideline for communication planning and communication management at WJSC events. This research uses a qualitative approach with a case study method, involving interviews, documentation and observation. This research refers to the PR strategy model of Cutlip, Center and Broom (2009), which involves four steps in the PR process, namely determining the problem, planning and programming, taking action and communicating, and program evaluation. The research results show that Eiger Adventure was successful in designing and implementing WJSC with an effective communication strategy. Even without carrying out special segmentation in its approach, in reality the number of WJSC registrants exceeds the target, which shows Eiger's reputation among nature activists.